A habilidade argumentativa e a capacidade de resolver problemas nos anos finais do ensino fundamental - Ruppenthal, Raquel (2017)
One of the goals of Science Teaching is to form autonomous individuals, critical, reflective, capable of solving impasses effectively. The central objective of this study was to investigate whether the use of pro-argumentation activities modify the argumentative levels and the problem-solving ability with a qualitative approach. It was used as resources for data collection instrument elaborated for analysis of arguments, test of the capacity to solve problems and interview. Students from the final years of Elementary School, from three schools (A, E, I), in the city of Ibirubá-RS, participated in the research. The instrument for the analysis of arguments was tested with students of the 6th grade of School I. It was verified the adequacy of the instrument as well as the relationship between the level of conceptual knowledge and the production of more elaborate arguments. The pilot study with the problem-solving test was carried out with 8th and 9th grade classes from school I, and it was convenient for later use, as well as pointing to students' difficulties with the Prediction and transfer factor. To achieve the central objective of the research, the argumentative level and the problem-solving capacity were described in three groups of 8th grade, of schools A, E and I, with low argumentative and problem solving levels. The class of the school I was interviewed in order to know the strategies used by the students to solve the test. It was observed that the greatest arsenal of strategies is related to the best performance in the problem solving test. This group participated in the intervention with pro-argumentation activity. After four months, it was observed that the statements of these students presented more elaborate reasoning strategies, such as the use of examples and comparisons to justify their arguments, which was not verified with the students of school A. The results suggest that the domain can be related to better performance in problem solving.